Fulfillment of basic psychological needs: a qualitative investigation of strategies used by elite youth soccer coaches - Raabe, J.; Readdy, T.; Höner, O. (German Journal of Exercise and Sport Research, 2020)
An optimal coaching style can result in the simultaneous fulfillment of individuals` basic psychological needs of competence, autonomy, and relatedness. According to self-determination theory, such need fulfillment increases the likelihood that athletes will experience self-determined motivation, which, in turn, has been found to positively affect their cognition, affect, and behavior. The purpose of the current research was to investigate specific strategies elite youth soccer coaches use that they believe nurture athletes` perceptions of competence, autonomy, and relatedness. Semi-structured interviews were conducted with 16 coaches from the German Soccer Association`s (Deutscher Fußball-Bund) talent identification and development program. Using thematic analysis, five themes were constructed: (a) Design task-oriented practices, (b) transfer tasks and responsibilities to players within boundaries, (c) support players in the development and implementation of optimal goals, (d) promote positive interactions within the team, and (e) show players appreciation independent of their performance. The present findings allow for a more nuanced understanding of need-supportive coaching and its application in the coach-athlete relationship.